2018
DOI: 10.1109/tmag.2018.2854663
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Surface Plasmon, Magneto-Optic Surface Plasmon, and Sensitivity Properties of Magneto-Plasmonic Co/Au Multilayers

Abstract: Microstructure properties of [Co 1. 2 nm / Au 2.0 nm] × N = 20 multilayers prepared using dcmagnetron sputtering is reported using X-ray reflectivity (XRR) and X-ray diffraction (XRD) analysis. XRR profiles of these multilayers showed excellent bilayer periodicity. The XRD spectra displayed Co layer thicknessdependent properties. However, annealing increased lateral tensile strain decreased compressive strain along the normal substrate direction. While surface roughness, crystallite grain size, and strain are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The chemical composition of the oxides was determined using a PW4025/00 MiniPal compact energy-dispersive X-ray spectrometer from PANalytical B.V. with an integrated rhodium lamp (for this reason a rhodium-derived peak is visible on each spectrum). In addition, using the XRD method, the size of the zinc-titanium oxide crystallites was determined using the calculated full width at half maximum of the reflections and the Debye-Scherrer method using the relationship between the broadening of the diffraction line profile and the size of the crystallites [32], described by the Formula (1):…”
Section: Methodsmentioning
confidence: 99%
“…The chemical composition of the oxides was determined using a PW4025/00 MiniPal compact energy-dispersive X-ray spectrometer from PANalytical B.V. with an integrated rhodium lamp (for this reason a rhodium-derived peak is visible on each spectrum). In addition, using the XRD method, the size of the zinc-titanium oxide crystallites was determined using the calculated full width at half maximum of the reflections and the Debye-Scherrer method using the relationship between the broadening of the diffraction line profile and the size of the crystallites [32], described by the Formula (1):…”
Section: Methodsmentioning
confidence: 99%
“…In the design of MOSPR sensors, complex nanostructures combined with magnetic materials and noble metals are usually used, which can eliminate the prism coupling mechanism and realize the miniaturization and integration of the device [11,16]. In addition, through geometric resonance, the nanostructures can further enhance the MO effect [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have observed decrement in surface roughness in the sample with annealing which further suggested improvement in layer periodicity and sharpening of interfaces. Such studies provide a base for possible fabrication of magnetic sensors and other devices like magnetoresistance devices, 33,34 X-ray and gamma ray optics, 35 magneto-plasmonics, 36 and to study their spin dependent conductivity. 33,36,37 However, a better knowledge of growth, structure along with the magnetic orientation, and pertaining magnetic domain structure of layers and their interfaces is worth studying.…”
Section: Introductionmentioning
confidence: 99%